Extraction and optimization of Microalgal Carbonic Anhydrase for biosequestration of Carbon Dioxide - L. BENEDICT BRUNO; S. SANDHYA; J. DEEPIKA; RAVI SHANKAR (International Journal of Pharma and Bio Sciences, 2017)
In the global effort to combat the predicted outcomes, several CO2 capture and storage technologies are being deliberated. One possibility rests on the use of carbonic anhydrase enzyme, which have been long known to accelerate the hydration of neutral aqueous CO2 molecules to ionic bicarbonate HCO3− species. The carbonic anhydrase (CA) activity were determined in two fresh water green algae Chlorella sp. and Scenedesmus pectinatus growing in laboratory condition. In the detailed experiment, the effects of various parameters such as nitrate, pH, salinity, phosphate and light intensity were studied. The study reveals that the activity of enzyme is induced by alkaline pH (6.5-7.5), nitrate, salinity, phosphate concentration in the range of 250 mg/l, 25mg/l and 175 mg/l K2HPO4 and 75mg/l KH2PO4 respectively. Although the experiments were carried out under controlled experimental conditions, they could provide some preliminary data that would prove useful for the control of algal bloom in nature.